2018
DOI: 10.26582/k.50.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Shorter sprints elicit greater cardiorespiratory and mechanical responses with less fatigue during time-matched sprint interval training (SIT) sessions

Abstract: The aim of this study was to compare the physiological, mechanical and perceptual responses to two sprint interval training (SIT) sessions with very short vs. long sprints, and to verify if those differences could be reflected in measures of acute fatigue. Eleven physically active men performed, after the maximum oxygen consumption (VO2max) determination, SIT5s (16×5s with 24s of recovery) and SIT20s (4×20s with 120s of recovery) in random order on a cycle ergometer. Physiological, mechanical, and perceptual r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 52 publications
2
35
4
Order By: Relevance
“…Can exercise be modulated to make it more rewarding, and thus result in greater “wants”? Exercise can be modified to increase enjoyment by focusing on preferences ( Stults-Kolehmainen et al, 2013 ; Busch et al, 2016 ) or reduce punishing aspects of exercise, like avoiding eccentric contractions ( Kerksick et al, 2009 ) or excessive buildup of lactate and fatigue (e.g., minimized with sprint interval training – SIT) ( Benitez Flores et al, 2018 ; de Sousa et al, 2018 ). It is likely important to avoid sudden, large increases in novel physical activities that result in excessive muscle damage and soreness, which are associated with decreases in physical activity ( Proske, 2005 ; Stults-Kolehmainen et al, 2014 ) and negative shifts in mood ( O’Connor et al, 1991 ; Stults-Kolehmainen and Bartholomew, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Can exercise be modulated to make it more rewarding, and thus result in greater “wants”? Exercise can be modified to increase enjoyment by focusing on preferences ( Stults-Kolehmainen et al, 2013 ; Busch et al, 2016 ) or reduce punishing aspects of exercise, like avoiding eccentric contractions ( Kerksick et al, 2009 ) or excessive buildup of lactate and fatigue (e.g., minimized with sprint interval training – SIT) ( Benitez Flores et al, 2018 ; de Sousa et al, 2018 ). It is likely important to avoid sudden, large increases in novel physical activities that result in excessive muscle damage and soreness, which are associated with decreases in physical activity ( Proske, 2005 ; Stults-Kolehmainen et al, 2014 ) and negative shifts in mood ( O’Connor et al, 1991 ; Stults-Kolehmainen and Bartholomew, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our protocols showed a lesser blood lactate accumulation than a remarkable number of previous designs that applied SIT or HIIT [ 11 ]. Overall, reduced durations of effort, regardless of the exercise modality used (i.e., cycling or running), seem to rely more on oxidative metabolism with less dependence on glycolytic metabolism, attenuating the residual fatigue [ 12 , 13 , 19 , 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…During each session, HR was instantaneously monitored and feedback was provided so that the subjects maintained the target intensity. Previously, our group identified that HR was equal to ~90% HR max in response to a very similar modified SIT protocol as the one used in the current study [ 19 ]. During SIT, participants were instructed to run as fast as they could for 5 s. After every repetition of HIIT and SIT, passive pauses were used to facilitate recovery [ 11 ], and then participants were warned by a sound signal to run in the opposite direction.…”
Section: Methodsmentioning
confidence: 99%
“…Can exercise be modulated to make it more rewarding, and thus result in greater "wants"? Exercise can be modified to increase enjoyment by focusing on preferences (148,149) or reduce punishing aspects of exercise, like avoiding eccentric contractions (150) or excessive buildup of lactate and fatigue (e.g., minimized with sprint interval training -SIT) (151,152). It is likely important to avoid sudden, large increases in novel physical activities that result in excessive muscle damage and soreness, which are associated with decreases in physical activity (153,154) and negative shifts in mood (155,156).…”
Section: Practical Implicationsmentioning
confidence: 99%